2017
DOI: 10.1136/oemed-2016-104051
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative estimated exposure to vinyl chloride and risk of angiosarcoma of the liver and hepatocellular cancer in the US industry-wide vinyl chloride cohort: mortality update through 2013

Abstract: ObjectiveTo evaluate mortality risks of angiosarcoma of the liver (ASL), primary hepatocellular carcinoma (HCC) and other cancers among 9951 men employed between 1942 and 1972 at 35 US vinyl chloride (VC) or polyvinyl chloride plants followed for mortality through 31 December 2013.MethodsSMR and time-dependent Cox proportional hazards analyses were used to evaluate mortality risks by cumulative VC exposure.ResultsLiver cancer mortality was elevated (SMR=2.87, 95% CI 2.40 to 3.40), and ASL and HCC were strongly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
53
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 31 publications
3
53
0
1
Order By: Relevance
“…The risk for both angiosarcoma of the liver and hepatocellular carcinoma increased for higher cumulative exposure. However, the actual incidence of angiosarcoma of the liver and hepatocellular carcinoma for workers employed after 1975 is lower than those employed before this time, with an increased latency period for the development of cancer in those employed after 1975 [45,53]. The link between liver cancer and VCM is now well established, with these results being witnessed in other studies, and further confirmed by the follow-up studies of these original cohorts [53][54][55][56].…”
Section: History Of Recognition Of Issues With Vcm and Setting Of Expsupporting
confidence: 67%
See 1 more Smart Citation
“…The risk for both angiosarcoma of the liver and hepatocellular carcinoma increased for higher cumulative exposure. However, the actual incidence of angiosarcoma of the liver and hepatocellular carcinoma for workers employed after 1975 is lower than those employed before this time, with an increased latency period for the development of cancer in those employed after 1975 [45,53]. The link between liver cancer and VCM is now well established, with these results being witnessed in other studies, and further confirmed by the follow-up studies of these original cohorts [53][54][55][56].…”
Section: History Of Recognition Of Issues With Vcm and Setting Of Expsupporting
confidence: 67%
“…However, an increased risk of liver cirrhosis, which is a risk factor for hepatocellular carcinoma, as a result of exposure has been observed in other studies [52]. This was not confirmed by either the US or European cohorts [53]. The risk for both angiosarcoma of the liver and hepatocellular carcinoma increased for higher cumulative exposure.…”
Section: History Of Recognition Of Issues With Vcm and Setting Of Expmentioning
confidence: 58%
“…Rather than concluding that associations observed suggested possible links between volatile airborne contaminants and HCC, they instead dropped any qualification when singling out VCM exposure and HCC. Strangely, the associations in the logistic regression for VCM were strongest for the shortest latency period, which is inconsistent with established epidemiology [2]. Nor do the authors account for the most likely cause of increased occurrence – hepatitis C or B virus infection [7] 4 .…”
mentioning
confidence: 67%
“…Those data were compared with hepatocellular carcinoma (HCC) rates from 2 time frames: 2000–2013 and 2006–2013. The latency period for angiosarcoma of the liver (ASL) and HCC is much longer than the 7- to 13-year duration used in the study (36–48 years) [2]. The time between measurement and observation periods for HCC is far too short.…”
mentioning
confidence: 99%
“…Specifically, a study examining vinyl chloride exposure and HCC risk reported that the median latency for HCC deaths was 48 years (range 31.5-66.6) [3]. Due to this, the exposure time points evaluated in this analysis are likely biologically irrelevant and inappropriate, as any impact on disease would not yet have been clinically diagnosed or detected.…”
mentioning
confidence: 99%